The peak locomotor characteristics of Super League (rugby league) match-play - Whitehead, S.; Barron, N. D.; Rennie, G.; Jones, B. (International Journal of Performance Analysis in Sport, 2021)
This study quantified the position-, duration-, and phase-of-play specific peak locomotor characteristics of senior professional rugby league match-play at a multi-club level. Match-play data were collected from 378 male professional rugby league players, from 11 clubs, across two competitive seasons. A total of 9643 match-observations were analysed; 10-Hz instantaneous velocity and acceleration from Catapult S5 microtechnology units were aligned with video footage to determine to the phase-of-play and duration-specific peak locomotor characteristics (average running speed, relative high-speed running [HSR;>5.5 m·s-1], average absolute acceleration). Linear mixed effect models were used to determine positional differences for each dependent variable and differences between phases-of-play. Positional differences for the duration-specific and phase-of-play peak locomotive characteristics were identified. Fullbacks had greater peak HSR during defensive sets (86 ± 70 m·min-1) vs. all other positions (effect size = 0.26 to 0.49, small). Wingers demonstrated the greatest between phase differences with greater peak locomotor characteristics (effect size = 1.23 to 1.65, large) during attacking-defensive set transition vs. defensive sets. The multi-club normative data, and the differences identified, provides practitioners with valuable information for the consideration of training practices; the incorporation of phases-of-play enables greater consideration of technical-tactical factors whilst preparing players for the peak periods of competition.